Retaliation Against Trump's Trade War: Why and How the EU Should Find Alternative Export Markets - Wim Naudé; Martin Cameron (Institute of Labor Economics (IZA), 2025)
In retaliating against Trump's March 2025 imposition of import tariffs on EU aluminum and steel, the EU's response should be twofold: one, at the EU level, to apply retaliatory tariffs and negotiations, and two, to support country-level efforts to minimize the impact of tariffs, including external substitution. We point out that the EU does not, however, at present seem to explicitly consider external substitution, i.e. finding alternative export markets. We show why this is an omission, and use the case of the Netherlands to illustrate how to find alternative export markets and how this can bolster the EU's retaliation effort. Our empirical modelling finds that while most of the Netherlands' exports to the USA are at low-to-medium risk, a smaller portion is at high risk. For aluminum and steel products, the high-risk products face exports-at-risk of US 245 million, much lower than some current estimates. For these, we identify alternative export opportunities outside the USA and EU. The USA's trade policies could push the Netherlands and the wider EU towards closer economic ties with other global players, potentially weakening the USA's geopolitical standing.
Keywords: F10; F13; F1; F17; 330; EU; Trump tariffs; USA tariffs; trade wars; export diversification